A palindrome-driven complex rearrangement of 22q11.2 and 8q24.1 elucidated using novel technologies - Gotter, Anthony L.; Nimmakayalu, Manjunath A.; Jalali, G. Reza; Hacker, April M.; Vorstman, Jacob; Duffy, Danielle Conforto; Medne, Livija; Emanuel, Beverly S. (Genome Research, 2007)
Constitutional translocations at the same 22q11.21 low copy repeat B (LCR-B) breakpoint involved in the recurrent t(11;22) are relatively abundant. A novel 46,XY,t(8;22)(q24.13;q11.21) rearrangement was investigated to determine whether the recurrent LCR-B breakpoint is involved. Investigations demonstrated an inversion of the 3Mb region typically deleted in patients with the 22q11.2 deletion syndrome. The 22q11.21 inversion appears to be mediated by low copy repeats, and is presumed to have taken place prior to translocation with 8q24.13. Despite predictions based on inversions observed in other chromosomes harboring low copy repeats, this 22q11.2 inversion has not been observed previously. The current studies utilize novel laser microdissection and MLPA (multiplex ligation-dependent probe amplification) approaches, as adjuncts to FISH, to map the breakpoints of the complex rearrangements of 22q11.21 and 8q24.21. The t(8;22) occurs between the recurrent site on 22q11.21 and an AT-rich site at 8q24.13, making it the fifth different chromosomal locus characterized at the nucleotide level engaged in a translocation with the unstable recurrent breakpoint at 22q11.21. Like the others, this breakpoint occurs at the center of a palindromic sequence. This sequence appears capable of forming a perfect 145 bp stem–loop. Remarkably, this site appears to have been involved in a previously reported t(3;8) occurring between 8q24.13 and FRA3B on 3p14.2. Further, the fragile site-like nature of all of the breakpoint sites involved in translocations with the recurrent site on 22q11.21, suggests a mechanism based on delay of DNA replication in the initiation of these chromosomal rearrangements.